Study on deformation characteristics of toppling failure of anti-dip rock slopes under different soft and hard rock conditions - Cai, Junchao; Wang, Junping; Li, Zhen; Kong, Yanli; Zhang, Liang; Qi, Guoqing (Frontiers in Earth Science, 2024)
For the widespread exposure of toppling deformation phenomena in anti-dip engineering slopes such as hydropower, transportation, and mining, especially deep-seated toppling, these large-scale deep-seated toppling deformations reaching depths of hundreds of meters have become significant geotechnical engineering problems that restrict large-scale engineering construction and require urgent solutions. There are significant differences in the failure characteristics and mechanisms of anti-dip rock slopes under different soft and hard rock conditions. This study, starting from the failure characteristics and mechanisms under different soft and hard conditions of rocks, summarizes two types of toppling deformation: ductile bending deep toppling(DBDT) and brittle fracture shallow toppling(BFST). The UDEC method is used to preliminarily explore the threshold of rock mechanical parameters for these two types of toppling, with 80MPa (UCS, Uniaxial compressive strength) mechanical parameters serving as the preliminary threshold. The results indicate that hard rock undergoes brittle fracture shallow toppling (BFST), while soft rock undergoes ductile bending deep toppling (DBDT). The rock mechanical parameters of 100MPa (UCS) and 20MPa (UCS) were selected to study the evolution process and mechanism of ductile bending deep toppling (DBDT) and brittle fracture shallow toppling (BFST) deformations, respectively. Numerical simulation results have innovatively revealed the mechanical behavior characteristics between rock layers during the process of toppling deformation. Due to the fact that toppling deformation mainly originates from interlayer displacement deformation and intra layer tensile deformation of rock layers, the interlayer mechanical characteristics is of great significance for understanding the mechanism of toppling deformation. This research can provide a theoretical basis for the stability assessment and development utilization of anti-dip rock slopes and toppled slopes.